2022
DOI: 10.1590/0102-311x00346520
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution and its risk for cardiovascular events in 10 years: Brazilian Longitudinal Study of Adult Health (ELSA-Brasil)

Abstract: Body fat distribution seems to have different effects in cardiovascular diseases (CVD). We aimed to estimate the associations between lower limbs and trunk fat ratio and the 10-year CVD risk, and isolated risk factors in men and women. A total of 10,917 participants from ELSA-Brasil were eligible for this cross-sectional study. Associations between lower limb/trunk fat ratio with the percentage of 10-year CVD risk - according to the Framingham Risk Score - and its risk factors (systolic blood pressure, total c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
(85 reference statements)
0
3
0
4
Order By: Relevance
“…In meta-regression analysis both waist circumference and the waist-to-hip ratio were associated with elevated incident CVD risk in both sexes ( 56 ). Recently, the Brazilian Longitudinal Study of Adult Health reported that a higher lower limb: trunk fat ratio was related to a reduced 10-year cardiovascular risk, mediated by lower systolic blood pressure, lower total cholesterol, and increased HDL-C levels ( 57 , 58 ). Central fat depots contain dysfunctional adipocytes characterized by a pro-inflammatory nature, restricted hyperplasia, and higher turnover of bioactive lipids.…”
Section: Discussionmentioning
confidence: 99%
“…In meta-regression analysis both waist circumference and the waist-to-hip ratio were associated with elevated incident CVD risk in both sexes ( 56 ). Recently, the Brazilian Longitudinal Study of Adult Health reported that a higher lower limb: trunk fat ratio was related to a reduced 10-year cardiovascular risk, mediated by lower systolic blood pressure, lower total cholesterol, and increased HDL-C levels ( 57 , 58 ). Central fat depots contain dysfunctional adipocytes characterized by a pro-inflammatory nature, restricted hyperplasia, and higher turnover of bioactive lipids.…”
Section: Discussionmentioning
confidence: 99%
“…Tras la profundización en el estudio de la obesidad y su asociación a patologías 51 , se ha cuestionado la utilización clínica individual del IMC, debido a la arbitrariedad en los puntos de corte, sumada la nula especificación de la cantidad de masa magra y distribución de grasa corporal 52 , por lo que, por sí solo puede clasificar erradamente como sobrepeso u obesidad 53,54 . Motivo por el cual, el IMC como dato único se debería utilizar para estudios de prevalencia en poblaciones, mas no para manejo de pacientes 55 .…”
Section: Controversia Del Uso Del Imcunclassified
“…Em análise multivariada, observou-se que a menor relação entre gordura nas extremidades/gordura no tronco foi protetora para a presença de diabetes em mulheres (0,04; IC 95% 0,01-0,19), mas não em homens (1,03; IC 95% 0,37-2,86). 333 • Dados da PNS de 2019 com 86.678 adultos mostraram que assistir televisão por mais de 3 horas por dia aumentou a chance de desenvolver diabetes em comparação a menos de 3 horas por dia (3-6 horas/dia vs. referência OR 1,26; IC 95% 1,12-1,42; >6 horas/dia vs. referência OR 1,80; IC 95% 1,54-2,11; ajustes para sexo, faixa etária, etnia, nível educacional, consumo de álcool, tabagismo, consumo de refrigerantes e frutas, e atividade física de lazer). Por outro lado, não houve associação entre o uso de outras telas (computadores, tablets e telefones celulares) e a chance de desenvolver diabetes.…”
Section: Prevalênciaunclassified
“…Em análise multivariada, observou-se que a menor relação entre gordura nas extremidades/gordura no tronco foi protetora para a presença de diabetes em mulheres (0,04; IC 95% 0,01-0,19), mas não em homens (1,03; IC 95% 0,37-2,86). 333 …”
Section: Fatores De Risco E Prevençãounclassified
See 1 more Smart Citation